REWARD AND PUNISHMENT ON EMPLOYEE PERFORMANCE THROUGH WORK DISCIPLINE AT PELABUHAN INDONESIA II (PERSERO) LTD PANJANG - Alfian, Firmansyah Yunialfi; Magdalena, Betty (Prosiding International conference on Information Technology and Business (ICITB), 2018)
The result of the path analysis showed that the significant value of the reward, the punishment, and the work discipline was smaller than the significant level (α = 0.05). Therefore, it was concluded that the reward and the punishment had thesignificant effect on the employee performance through the work discipline at Pelabuhan Indonesia II (Persero) Ltd., Panjang. It indicated that the high rewards brought employees aware of and improved the employees’ quality so that the employees were more disciplined. Moreover, the punishment (firm sanction) also brought employees to be more disciplined and to follow the company rules so that the employee performance improved. Keywords: Reward, Punishment, Work Discipline, Performance